UNDER A WHITE SKY : the nature of the future. - KOLBERT, ELIZABETH (THE BODLEY HEAD LTD, 2021)
The Pulitzer Prize-winning author of The Sixth Extinction returns to humanity's transformative impact on the environment, now asking: After doing so much damage, can we change nature, this time to save it? That man should have dominion "over all the earth, and over every creeping thing that creepeth upon the earth" is a prophecy that has hardened into fact. So pervasive are human impacts on the planet that it's said we live in a new geological epoch: the Anthropocene. In Under a White Sky, Elizabeth Kolbert takes a hard look at the new world we are creating. She meets scientists who are trying to preserve the world's rarest fish, which lives in a single, tiny pool in the middle of the Mojave. She visits a lava field in Iceland, where engineers are turning carbon emissions to stone; an aquarium in Australia, where researchers are trying to develop "super coral" that can survive on a hotter globe; and a lab at Harvard, where physicists are contemplating shooting tiny diamonds into the stratosphere in order to reflect sunlight back to space and cool the earth. One way to look at human civilization, says Kolbert, is as a ten-thousand-year exercise in defying nature. In The Sixth Extinction, she explored the ways in which our capacity for destruction has reshaped the natural world. Now she examines how the very sorts of interventions that have imperiled our planet are increasingly seen as the only hope for its salvation. By turns inspiring, terrifying, and darkly comic, Under a White Sky is an utterly original examination of the challenges we face.